HSP70 and their co-chaperones in the human malaria parasite P. falciparum and their potential as drug targets - Barth, Julian; Schach, Tim; Przyborski, Jude M. (Frontiers in Molecular Biosciences, 2022)
As part of their life-cycle, malaria parasites undergo rapid cell multiplication and division, with one parasite giving rise to over 20 new parasites within the course of 48 hours. To support this, the parasite has an extremely high metabolic rate and level of protein biosynthesis. Underpinning these activities, the parasite encodes a number of chaperone/heat shock proteins, belonging to various families. Research over the past decade has revealed that these proteins are involved in a number of essential processes within the parasite, or within the infected host cell. Due to this, these proteins are now being viewed as potential targets for drug development, and we have begun to characterize their properties in more detail. In this article we summarize the current state of knowledge about one particular chaperone family, that of the HSP70, and highlight their importance, function, and potential co-chaperone interactions. This is then discussed with regard to the suitability of these proteins and interactions for drug development.